Pengaruh Kemudahan Penggunaan Dan Keamanan Terhadap Minat Penggunaan Shopee Paylater - Muhammad Rizza Sabit Banani; Evi Selvi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to find out how much easy of use influence and security have on the intention to use Shopee Paylater. This research method uses quantitative methods with descriptive verification. The data collection technique used in this study was respondent data that researchers collected as many as 377 respondents and previous studies. This study uses path analysis to find out how much influence easy of use and security have on intention to use. The significance value of easy of use was (0.000) < (0.05) and security (0.000) < (0.05), the easy of use and security variables had a significant positive influence on intention to use with a total influence of 45.1% and 54.9% influenced by other variables that were not studied.